Pelatihan Bisnis Merangkai Buket Bunga Sebagai Upaya Untuk Meningkatkan Pendapatan dan Kesejahteraan Rumah Tangga - Meidawati, Neni; Setyono, Primanita; Nustini, Yuni; Hudayati, Ataina; Laksmi, Ayu Chairina; Rahayu, Isti; Marfuah; Cahyawati, Noor Endah; Yendrawati, Reni; Prabowo, Hendi Yogi (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
Every house has a yard that can be used to cultivate plants, especially flower plants. A variety of flower plants can live in Indonesia. Flower plants can be used as a source of income. Flower plants can be sold directly, used for family celebrations, wedding anniversaries, graduations and so on. The aim of the community service is to increase the role of housewives in order to increase their awareness toward natural resources around them, especially flowers which are very easy to cultivate. The method used is training given to the members of Pemberdayaan dan Kesejahteraan Keluarga (PKK), and inviting professional trainers in making flower bouquets. Hopefully the training through the community service program can provide skills for PKK members to improve the family economy through the use of flower cultivation.